World Englishes at the grassroots - Meierkord, Christiane; Schneider, Edgar W. (Edinburgh University Press, 2021)
Bringing together an international range of contributors, this book explores face-to-face uses of English in a range of grassroots multilingual contexts.
Keywords: English language -- Foreign countries.; Anglais (Langue) -- Pays étrangers.; LANGUAGE ARTS & DISCIPLINES / Linguistics / Historical & Comparative; English language -- Foreign countries